The Impact of Injectable Opioid Agonist Treatment (iOAT) on Involvement in Criminalized Activities: A Secondary Analysis from a Clinical Trial in Vancouver, BC - Dobischok S; Guh D; Marchand K; MacDonald S; Lock K; Harrison S; Lajeunesse J; Schechter MT; Oviedo-Joekes E (Dove Medical Press, 2023)
Sophia Dobischok,1,2 Daphne Guh,2 Kirsten Marchand,2 Scott MacDonald,3 Kurt Lock,2,4 Scott Harrison,3 Julie Lajeunesse,3 Martin T Schechter,2,5 Eugenia Oviedo-Joekes2,5 1Department of Education and Counselling Psychology, McGill University, Montreal, QC, Canada; 2Centre for Advancing Health Outcomes, Providence Health Care, Vancouver, BC, Canada; 3Providence Health Care, Providence Crosstown Clinic, Vancouver, BC, Canada; 4BC Centre for Disease Control, Provincial Health Services Authority, Vancouver, BC, Canada; 5School of Population and Public Health, University of British Columbia, Vancouver, BC, CanadaCorrespondence: Eugenia Oviedo-Joekes, Centre for Advancing Health Outcomes, St. Paul's Hospital, 575-1081 Burrard St, Vancouver, BC, V6Z 1Y6, Canada, Tel +1 604-682-2344 Ext. 62973, Fax +1-604-806-8210, Email eugenia.joekes@ubc.caPurpose: A significant portion of the economic consequences of untreated Opioid Use Disorder (OUD) relate to individuals' involvement in the criminal justice system. The present study uncovers if treatment with iOAT is related to the number of criminal charges amongst participants, what type of crime participants were involved in, and the frequency with which participants were victims of crime. This study contributes to the body of research on the effectiveness of iOAT reducing criminal involvement.Patients and Methods: This is a secondary analysis of police record data obtained from the Vancouver Police Department over a three-year period during the Study to Assess Longer-term Opioid Medication Effectiveness clinical trial. The data was obtained from participants (N = 192) enrolled in the trial through a release of information form.Results: During the three-year period, most charges (45.6%) were property offences, and 25.5% of participants were victims of crime. Participants with no treatment prior to randomization into the SALOME trial were 2.61 (95% CI = 1.64- 4.14) more likely to have been charged with a crime than during the iOAT state.Conclusion: IOAT can reduce individuals' involvement with the criminal justice system and is thus a crucial part of the continuum of care. Addiction should be conceptualized as a healthcare rather than criminal issue.Keywords: heroin assisted treatment, diacetylmorphine, hydromorphone, crime, charges, police